Green Arrow : year one - Diggle, Andy.; Jock, 1972- (New York : DC Comics, 2008)
Traces the origins of Green Arrow Oliver Queen, a rich outdoor adventurer who finds himself stranded on an island where he fights for survival against the elements and the drug runners who left him to die.
"Originally published in single magazine form in Green Arrow: Year One #1-6"--T.p. verso.
Young Adult
Keywords: Archers -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc. -- Fiction; Green Arrow (Fictitious character) -- Comic books, strips, etc. -- Fiction; Superheroes -- Comic books, strips, etc. -- Fiction; Archers -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Good and evil -- Comic books, strips, etc. -- Fiction; Graphic novels; Green Arrow (Fictional character) -- Comic books, strips, etc. -- Fiction; Superhero graphic novels; Superheroes -- Comic books, strips, etc. -- Fiction; Graphic novels; Superhero comic books, strips, etc